2020
DOI: 10.9734/air/2020/v21i530204
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antibacterial Assay of Some Schiff Base Metal (II) Complexes

Abstract: The complexes of Co (II), Mn (II) and Ni (II) with Schiff base derived from pentane-2, 4-dione and 2-aminobenzoic acid were synthesized and characterized by molar conductivity, magnetic susceptibility, Infrared and elemental analyses. The solubility test on the Schiff base and its metal (II) complexes revealed their solubility in most organic solvents except chloroform and diethyl ether. The molar conductivity of the complexes was small indicating that they are non-electrolytes. The antibacterial susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[11] 2-hydroxy benzaldehyde and 2-amino benzoic acid take part in the formation of Schiff base. The ligand characterized by solubility test [12] . The proposed formula of salicyladehyde and anthranilic acid of both transitional element and inner transitional element are considerably utilize in the work of co-ordination chemistry.…”
Section: Importance Of Schiff Base:-mentioning
confidence: 99%
“…[11] 2-hydroxy benzaldehyde and 2-amino benzoic acid take part in the formation of Schiff base. The ligand characterized by solubility test [12] . The proposed formula of salicyladehyde and anthranilic acid of both transitional element and inner transitional element are considerably utilize in the work of co-ordination chemistry.…”
Section: Importance Of Schiff Base:-mentioning
confidence: 99%
“…The empirical formula determination indicated the formation of a 1:1 metal-to-ligand complexes [7] . Uba et al reported the complexation of Co(II), Mn(II) and Ni(II) with a Schiff base derived from the condensation of pentane-2,4dione and 2-aminobenzoic acid [8] . The synthesized compounds were characterized by molar conductivity, infrared spectroscopy and elemental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The molar conductance values of the complexes were small, suggestive of their non-electrolytic nature. The compounds were assayed for antibacterial activity and were found, with exception of the Ni(II) complex, to show good activity [8] .…”
Section: Introductionmentioning
confidence: 99%